EFEK BERGANDA (MULTIPLIER EFFECT) PT. HUTAN KETAPANG INDUSTRI TERHADAP USAHA MASYARAKAT DUSUN SILINGAN DAN DUSUN KLUKUBLANTAK DESA MEKAR UTAMA KECAMATAN KENDAWANGAN KABUPATEN KETAPANG - Rahadi, Jimi; Roslinda, Emi; Idham, M (JURNAL HUTAN LESTARI, 2019)
Industrial plantations (HTI) are plantations established by industrial groups to increase the potential and quality of production forests by implementing silvicultural systems in order to meet the needs of raw materials. PT. HKI is one of the HTI engaged in the industry which is located in Silingan and Klukublantak sub-villages, Mekar Utama Village, Kendawangan District. The existence of PT. HKI impacts business actors, workers, and the community around the PT. HKI. Therefore it is necessary to analyze the economic impact caused by PT. HKI. The purpose of this study is to examine the characteristics and perceptions of business people, workers, and the community, and examine the multiplier effect on the existence of PT. HKI. This research uses the respondent sampling method with quota sampling technique. Respondents in this study were 90 people divided into 30 business people, 30 workers, and 30 people. Data analysis uses descriptive analysis and multiplier effect analysis of the characteristics of business people, workers, and the public in PT. HKI. Characteristics of respondents in PT. HKI is dominated by men. The perception of business people, workers, and the community tends to be positive. The economic impact can be seen from the Keynesian Income Multiplier value obtained at 3.25 while the Type 1 Multiplier Income Ratio is 1.19 and the Type 2 Multiplier Income Ratio is 1.29. Based on this it can be concluded that PT. HKI provides an economic impact on businesses and workers in the area of PT. HKI.Keywords: Characteristics, Multiplier effect, Perception.